PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Veronika Mau, Maria; Muslichah, Muslichah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2026)
This research was conducted with the aim of testing the effect of profitability and leverage as independent variables on company value as the dependent variable and corporate social responsibility as a moderating variable. The method used is quantitative causality with a descriptive approach, the data source is secondary data from financial reports of companies in the consumer goods industry for the period 2018-2022. The population found was 75 companies, while the final sample sorted based on purposive sampling was 38 companies. Based on the interpretation algorithm using SmartPLS software, the results obtained in this research are that profitability has no effect on company value, leverage has an effect on company value, and CSR is unable to moderate the relationship between profitability and leverage on company value.